Supramolecular self-assembly for generation of nanostructures - Chua, Kee Sze. (2013)
Block copolymers have a wide array of applications in nanofabrication due to their consistent and controllable micelle morphology and have vast potential in the field of nanoparticles assembly. The selective interaction of these nanoparticles with particular blocks of the copolymer brings about interesting assembly patterns with tuneable dimensions. The alignment of these nanocrystals with block copolymers allows the control of morphology features and their dimensions. In this thesis, the block copolymer polystyrene-poly(4-vinyl pyridine) (PS-P4VP) was studied as a tool for nanofabrication in photovoltaic devices. Polar additives were added to the block copolymer and subsequently removed to generate pores and grooves.